The characteristics of asbestos-related disease claims made to the Korea Workers’ Compensation and Welfare Service (KCOMWEL) from 2011 to 2015 - An, Yon Soo (Ann Occup Environ Med, 2018)
BACKGROUND: This study aimed to enhance understanding of the epidemiologic characteristics of asbestos-related diseases, and to provide information that could inform policy-making aimed at prevention and compensation for occupational asbestos exposure, through analyzing asbestos-related occupational disease claims to Korea Workers’ Compensation and Welfare Service from 2011 to 2015. METHODS: We analyzed 113 workers who filed medical care claims or survivor benefits for asbestos exposure and occupational-related disease from 2011 to 2015. Among these claims, we selected approved workers’ compensation claims relating to malignant mesothelioma and lung cancer, and analyzed the general characteristics, exposure characteristics, pathological characteristics, and occupation and industry distribution. RESULTS: Malignant mesothelioma and lung cancer occurred predominantly in males at 89.7 and 94%, respectively. The mean age at the time of diagnosis for malignant mesothelioma and lung cancer was 59.5 and 59.7 years, respectively, while the latency period for malignant mesothelioma and lung cancer was 34.1 and 33.1 years, respectively. The companies involving exposed workers were most commonly situated within the Busan-Ulsan-Gyeongnam region. Histology results for lung cancer indicated adenocarcinoma as the most common form, accounting for approximately one half of all claims, followed by squamous cell carcinoma, and small cell lung cancer. The most common occupation type was construction in respect of malignant mesothelioma, and shipbuilding in respect of lung cancer. CONCLUSIONS: Considering the long latency period of asbestos and that the peak period of asbestos use in Korea was throughout the mid-1990s, damage due to asbestos-related diseases is expected to show a continued long-term increase. Few studies providing an epidemiologic analysis of asbestos-related diseases are available; therefore, this study may provide baseline data to assist in predicting and preparing for future harm due to asbestos exposure. TRIAL REGISTRATION: DUIH 2018–02–004-001. Registered 28 Februrary 2018.